Immunostimulation and increase of intestinal lactic acid bacteria with dietary mannan-oligosaccharide in Nile tilapia juveniles - Levy-pereira, Nycolas; Yasui, George Shigueki; Cardozo, Marita Vedovelli; Dias Neto, José; Farias, Thaís Heloísa Vaz; Sakabe, Roberson; Pádua, Santiago Benites De; Pilarski, Fabiana (Sociedade Brasileira de Zootecnia, 2018)
ABSTRACT In this experiment, the beneficial effects of mannan-oligosaccharide (MOS) on immunology and intestinal microbiology of Nile tilapia juveniles was demonstrated. Prior to this, three levels of MOS in Nile tilapia diets (1, 8, and 15 g.kg−1) were tested, and hematological parameters, serum lysozyme, and intestinal microbiology were analyzed. The fish blood was sampled at day zero (basal sample) and after 45 days of trial, and the intestinal microbiota was evaluated at the end of the experiment. After 45 days of trial, fish fed 8 and 15 g.kg−1 of MOS presented an increase in both aerobic and lactic acid bacteria numbers in their guts. The MOS feeding also increased the counts of total leukocytes, monocytes, and lymphocytes of fish, but a decrease in neutrophils was also observed. Additionally, the serum lysozyme was higher in all fish fed MOS. The dietary MOS is able to modulate the intestinal microbiota, increasing the number of beneficial bacteria, and immunostimulates the Nile tilapia juvenile, giving rise to white blood cells and serum lysozyme.
Keywords: aquaculture; hematology; intestinal microbiota; lysozyme; prebiotic